Factors Associated With Employment and Quality of Working Life in Patients With Metastatic Breast Cancer - Alina Kias; Martina E. Schmidt; Anouk E. Hiensch; Dorothea Clauss; Evelyn M. Monninkhof; Mireia Pelaez; Jon Belloso; Nadira Gunasekara; Maike G. Sweegers; Mark Trevaskis; Helene Rundqvist; Jana Müller; et al. (Cancer Medicine)
ABSTRACT Purpose As survival of patients with metastatic breast cancer (MBC) improves, their work situation is gaining importance. The aim of the current study was to identify factors associated with work status and quality of working life (QWL) in patients with MBC. Additionally, we investigated the effects of an exercise intervention on work status. Methods Within the multinational PREFERABLE‐EFFECT exercise trial, 287 patients with MBC of working age (18–65 years) reported on their working situation over 9 months as a secondary endpoint. Among a subgroup of participants, QWL was assessed by the Quality of Working Life Questionnaire for Cancer Survivors (QWLQ‐CS) (N = 59). Results At baseline, 157 (54.7%) participants were employed, of whom one‐third reported having recently reduced their amount of work because of fatigue (41.7%), cognitive problems (33.3%), or inability to meet work demands (33.3%). Participants wished for more flexible working hours (29.2%) and less productivity pressure (37.5%). Participants were less likely to work if they experienced higher levels of pain (p = 0.014). Among working participants, an academic education and higher levels of psychological distress were associated with a higher number of working hours (all p < 0.05). Fatigue, an academic education, and performing mentally strenuous tasks at work were negatively associated with QWL (all p < 0.05). The exercise intervention did not affect the number of hours worked during the study. Conclusions Symptom management might be important for patients' ability to work. To help patients stay employed and improve QWL, employers should consider offering more flexible work arrangements and adapting to their employees' changing needs and abilities. Trial Registration: The PREFERABLE‐EFFECT trial was registered with ClinicalTrials.gov on October 9, 2019 (NCT04120298).